My soul to keep eaudiobook African immortals series, book 1. - Due, Tananarive (African Immortals, 2002)
The award-winning master of horror, acclaimed author, screenwriter, and scholar Tananarive Due's classic African Immortals series starts with an electrifying piece of dark fantasy, My Soul to Keep. When Jessica marries David, he is everything she wants in a family man: brilliant, attentive, ever youthful. Yet she still feels something about him is just out of reach. Soon, as people close to Jessica begin to meet violent, mysterious deaths, David makes an unimaginable confession: More than 400 years ago, he and other members of an Ethiopian sect traded their humanity so they would never die, a secret he must protect at any cost. Now, his immortal brethren have decided David must return and leave his family in Miami. Instead, David vows to invoke a forbidden ritual to keep Jessica and his daughter with him forever. Harrowing, engrossing and skillfully rendered, My Soul to Keep traps Jessica between the desperation of immortals who want to rob her of her life and a husband who wants to rob her of her soul. With deft plotting and an unforgettable climax, this tour de force that Stephen King called "an eerie epic" is sure to win Due a legion of new fans.